Intelligent device system to monitoring indoor plant’s condition / Andi Mohammad Rezza Andi Amiruddin - Andi Amiruddin, Andi Mohammad Rezza (2024)
Home plant care entails giving adequate watering, sunlight, and nutrients to encourage growth and health. Regular monitoring, pruning, and pest management are required to keep indoor plants lively and healthy. People frequently neglect the demands of indoor plants in the midst of their hectic daily routines. Neglected watering, poor sunlight, and care deny these green companions the attention it deserves, negatively harming its vitality and overall well being. This technical report describes the creation of a smart monitoring system for home plants that uses a NodeMCU module to regulate appliances, especially for people who are unable to taking good care of the plants due to their priority and daily routine. The objective of this project is to design and develop a prototype of an automatic watering system for indoors plant. This report aims to design Intelligent Device System for Monitoring Indoor Plant’s Condition using Arduino Microcontroller. There are 5 inputs being in this project to detect the light intensity, soil moisture, temperature, and the presence of insect. These 5 inputs then will give results as the output for this project which can supply enough nutrient and the suitable environment for the home plants. This project will make it easier the people to monitoring, treating, and effectively pruning the indoor plants during workday or busy with daily routine.